2022
DOI: 10.3389/fimmu.2022.1010764
|View full text |Cite
|
Sign up to set email alerts
|

cGAS deficiency enhances inflammasome activation in macrophages and inflammatory pathology in pristane-induced lupus

Abstract: IntroductionType I interferon (IFN) plays a vital role in the pathogenesis of systemic lupus erythematosus. Cyclic GMP AMP synthase (cGAS) is a cytosolic DNA sensor that recognizes dsDNA and creates cGAMP to activate STING-mediated type I IFN production. The activation of STING induces lupus disease in Fcgr2b deficient mice through the differentiation of dendritic cells. In contrast, Cgas-deficient mice could be generated more autoantibody production and proteinuria in pristane-induced lupus (PIL). These data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…cGAS deficiency enhances lupus-like symptoms and inflammatory pathology in a pristane-induced mouse model of lupus [87]. cGAS deficiency also increases the expression of the caspase-11 gene, leading to activation of the caspase-11 non-canonical inflammasome in the lungs of pristane-induced lupus mice [87]. These results suggest that the caspase-11 noncanonical inflammasome is activated during SLE pathology by increasing caspase-11 expression, which is inhibited by cGAS.…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 89%
See 1 more Smart Citation
“…cGAS deficiency enhances lupus-like symptoms and inflammatory pathology in a pristane-induced mouse model of lupus [87]. cGAS deficiency also increases the expression of the caspase-11 gene, leading to activation of the caspase-11 non-canonical inflammasome in the lungs of pristane-induced lupus mice [87]. These results suggest that the caspase-11 noncanonical inflammasome is activated during SLE pathology by increasing caspase-11 expression, which is inhibited by cGAS.…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 89%
“…Kumpunya et al, demonstrated the functional cooperation of the caspase-11 non-canonical inflammasome with cyclic GMP AMP synthase (cGAS) during SLE pathogenesis in a murine lupus model. cGAS deficiency enhances lupus-like symptoms and inflammatory pathology in a pristane-induced mouse model of lupus [87]. cGAS deficiency also increases the expression of the caspase-11 gene, leading to activation of the caspase-11 non-canonical inflammasome in the lungs of pristane-induced lupus mice [87].…”
Section: Systemic Lupus Erythematosus (Sle)mentioning
confidence: 99%
“…The pathology grading from kidney sections was blinded by an experienced researcher. As previously described, the histology scores were reported as glomerular and interstitial scores 38 39 . In brief, glomerular scores were defined as 0 = normal; 1 = focal, mild, or early proliferative; 2 = moderate or definite proliferative; 3 = diffuse and focal or diffuse proliferative; 4 = severe diffuse proliferative with crescent/sclerosis, and interstitial scores were defined as 0 = normal; 1 = focal or small pockets (10–15 cells) of mononuclear cells (MNC); 2 = focal infiltrates (15–30 cells); 3 = multifocal extensive infiltrates with necrosis; 4 = multifocal or diffuse and extensive with necrosis.…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability (eBioscience™ Fixable Viability Dye eFluor™ 780, #65-0865-14, Thermo Fisher Scientific, CA, USA). For cell surface marker staining, splenocytes were isolated and prepared as previously described 32 .…”
Section: Methodsmentioning
confidence: 99%